Two fixed-point theorems for mappings satisfying a general contractive condition of integral type - B. E. Rhoades (International Journal of Mathematics and Mathematical Sciences)
We establish two fixed-point theorems for mappings satisfying a general contractive inequality of integral type. These results substantially extend the theorem of Branciari (2002).